Unexpected functional versatility of the pentatricopeptide repeat proteins PGR3, PPR5 and PPR10. Issue 19 (16th August 2018) - Rojas, Margarita; Ruwe, Hannes; Miranda, Rafael G; Zoschke, Reimo; Hase, Nora; Schmitz-Linneweber, Christian; Barkan, Alice
Abstract: Pentatricopeptide repeat (PPR) proteins are a large family of helical repeat proteins that bind RNA in mitochondria and chloroplasts. Sites of PPR action have been inferred primarily from genetic data, which have led to the view that most PPR proteins act at a very small number of sites in vivo . Here, we report new functions for three chloroplast PPR proteins that had already been studied in depth. Maize PPR5, previously shown to promote trnG splicing, is also required for rpl16 splicing. Maize PPR10, previously shown to bind the atpI-atpH and psaJ-rpl33 intercistronic regions, also stabilizes a 3′-end downstream from psaI . Arabidopsis PGR3, shown previously to bind upstream of petL, also binds the rpl14-rps8 intercistronic region where it stabilizes a 3′-end and stimulates rps8 translation. These functions of PGR3 are conserved in maize. The discovery of new functions for three proteins that were already among the best characterized members of the PPR family implies that functional repertoires of PPR proteins are more complex than have been appreciated. The diversity of sequences bound by PPR10 and PGR3 in vivo highlights challenges of predicting binding sites of native PPR proteins based on the amino acid code for nucleotide recognition by PPR motifs.